The territorial shaping of knowledge dynamics in Baden-Württemberg - Inter-organizational relations in the sectoral knowledge domain of the automotive industry - Simone Strambach; Iris Dieterich (Philipps-University Marburg, Department of Geography, 2011)
The paper focuses on the territorial shaping of knowledge dynamics as one of the driving forces for innovation. Knowledge dynamics are unfolding from processes of creation, use, transformation and diffusion of knowledge. Due to both the ongoing restructuring of global value chains and the changes in the organization of innovation 'combinatorial knowledge dynamics' gain a more prominent role in innovation. Firms are facing an increasing need to combine heterogeneous knowledge sources spread over organizational, technological, sectoral and spatial boundaries in innovation processes. Combinatorial knowledge dynamics imply to cope with many different cognitive, technological, intra- and inter-organizational and institutional interfaces. Deeper empirical investigation in the connected organizational and institutional change linked with knowledge dynamics is still missing, but is indeed necessary to better understand the spatio-temporality of knowledge dynamics behind innovation. Addressing the connection of space as a scope of action and space as being generated as a part of the social process, the paper chose a biographical method to explore knowledge dynamics.
Keywords: D83; L62; O32; 330; Innovation; territorial knowledge dynamics; automotive industry; Baden-Württemberg